Synthesis of siRNAs incorporated with cationic peptides R8G7 and R8A7 and the effect of the modifications on siRNA properties. Issue 57 (21st September 2020) - Matsubara, Miho; Honda, Kenji; Ozaki, Koki; Kajino, Ryohei; Kakisawa, Yuri; Maeda, Yusuke; Ueno, Yoshihito
Abstract : Small interfering RNA (siRNA) can be used as an innovative next-generation drug. Abstract : Small interfering RNA (siRNA) can be used as an innovative next-generation drug. However, there are several challenges in the therapeutic application of siRNAs, including their low cell membrane permeability. In this study, we designed and synthesized siRNAs, incorporating the cationic peptides R8G7 and R8A7 to improve cell membrane permeability of siRNAs. Thermal denaturation studies revealed that R8G7 and R8A7 modifications increased the thermal stability of the siRNA duplexes. Incorporating these peptides at the 3′-ends of the siRNA passenger strands increased the stability of the siRNAs in a buffer containing bovine serum. Further, we found that the peptide–siRNA conjugates did not show sufficient RNA interference (RNAi) activity in the absence of the transfection reagent; however, when the transfection reagent was used, the peptide–siRNA conjugates preserved their RNAi activity.